Lies in Plato’s Republic: poems, myth, and noble lie - Yu-Jung, Sun (ΠΗΓΗ/FONS, 2017)
In this paper, I argue that 1) the ostensible inconsistency between the judgments of value on different kinds of lying, like poetry, fabricated story, myth and noble lies, is not a veritable one, and 2) Plato does not hold a utilitarian position on the question of lying, or making up something false to be more precise, and lies do not turn into noble lies once they are told to be in the service of some superior purpose. Plato does state in Book II of the Republic that the veritable lie (ἀληθῶς ψεῦδος) is what all gods and all man hate (382a), and poets must be punished for deceiving people by linking the Supreme Being to its contrary. But Plato also discusses the useful lie, especially the one lie that is necessary for the unity and stability of the polis: the Noble Lie. Neither useful lies nor noble lies can be acceptable just because we can make a use out of it, and it does not hold either that the greater the use we can make out of a lie, the nobler a lie is. A true lie (ἀληθῶς ψεῦδος) for Plato is the kind of lie leading people to believe that the hierarchy of the forms can be reordered in any way, and we can make random associations between the forms, like forming the relation between gods and the action of war. On the other hand, useful lies and the noble lies are in fact a duplicate of the order of the forms. This order, which articulates forms, is what makes thinking of truth possible, and we can later find this idea of the order of the forms which allows us to think truth and falsity in both the Theaetetus and the Sophist.